Influenza virus and the new Influenza A/H1N1 pandemics - Talledo, Miguel (2009)
The Influenza virus belongs to the Orthomyxoviridae family, viruses with a negative sense segmented RNA genome. The influenza virus type A infects humans and other organisms, and is the causative agent of human influenza. Hemagglutinin and Neuraminidase stand out among other proteins, and are used in the classification of the members of this group. These viruses mutate continuously, with patterns long studied, the antigenic shift and the antigenic drift, with one major event of recombination called reassortment. All subtypes exist in wild aquatic birds, although other hosts can be found, such as horses, minks, whales, seals, pigs, hens and turkeys, among others. As part of its progressive adaptation to the human host, wild birds and poultry play a fundamental role as well as swine. Although H2N2 and H3N2 subtypes have been very common among the human population, H1N1 subtype has re-emerged with mutations that have allowed it to reach the pandemics state in 2009. This new virus has a close ancestor in a triple reassortant virus from a human influenza virus, a classic influenza swine virus and an avian influenza virus, and contains as well genetic segments from a Euroasian swine influenza virus. This has caused that the virus displays a mild disease, only severe or lethal in individuals with previous medical history. At worldwide level it has caused more than 134.510 cases and in Peru they are close to 3.700. The current state indicates that in Peru the pandemics is about to reach its peak due to the high morbidity of the virus and coldest season of the year. The containment of this virus is important, since the greater the number of people infected, the greater the number of reassortment events the virus will be subjected to, with previous human influenza viruses, and may determine the appearance of new strains, for which the immune system might not be prepared at the population level.